Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
The Oxford Handbook of Human Motivation 2012
DOI: 10.1093/oxfordhb/9780195399820.013.0018
|View full text |Cite
|
Sign up to set email alerts
|

The Gendered Body Project: Motivational Components of Objectification Theory

Abstract: In this chapter, we attempt to explore the motivational questions that arise when we view the psychology of women through the lens of objectification theory, which highlights the centrality of appearance concerns, or “body projects,” for girls and women today. We examine theoretical perspectives on what motivates the sexual objectification of women, considering the ways this treatment may reflect an adaptive evolutionary mating strategy, may serve as a tool for the maintenance of patriarchal power, or may lend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…Objectification theory is, however, a decidedly feminist theory, and as such explanations rooted in evolutionary heritage are suspect from our perspective, not only because they provide little hope in the way of remediation but also because they have not been satisfactorily empirically validated. Roberts and Waters (2012) critiqued this view by pointing to evidence that much interpersonal sexual objectification by men is not a reflection of them wanting to mate, nor are women's efforts at appearance enhancement typically a strategy for mating. Furthermore, eye gaze studies have not shown that attractiveness judgments of female bodies zero in on "fertility features," such as waist-to-hip ratio (e.g., Cornelissen, Hancock, Kiviniemi, George, & Tovee, 2009), and bogus pipeline studies have shown that men report significantly less engagement in sexual intercourse than do women (Fisher, 2013).…”
Section: Theoretical Perspectives On Sexual and Self-objectification'...mentioning
confidence: 99%
“…Objectification theory is, however, a decidedly feminist theory, and as such explanations rooted in evolutionary heritage are suspect from our perspective, not only because they provide little hope in the way of remediation but also because they have not been satisfactorily empirically validated. Roberts and Waters (2012) critiqued this view by pointing to evidence that much interpersonal sexual objectification by men is not a reflection of them wanting to mate, nor are women's efforts at appearance enhancement typically a strategy for mating. Furthermore, eye gaze studies have not shown that attractiveness judgments of female bodies zero in on "fertility features," such as waist-to-hip ratio (e.g., Cornelissen, Hancock, Kiviniemi, George, & Tovee, 2009), and bogus pipeline studies have shown that men report significantly less engagement in sexual intercourse than do women (Fisher, 2013).…”
Section: Theoretical Perspectives On Sexual and Self-objectification'...mentioning
confidence: 99%
“…Widdows suggests that a young, firm, smooth and thin physique has become an almost universal moral ideal [152]. A counter-movement challenging the objectification of the (female) physique and advocating 'body positivity' does not seem to have had much impact yet [153][154][155]. In aestheticised societies, attractiveness and ugliness are likely to be constitutive elements of the class structure.…”
Section: Attractiveness and Aestheticisationmentioning
confidence: 99%
“…Authors who have focused on the negative outcomes of being objectified (e.g., Fredrickson & Roberts, 1997;Marx, 1857Marx, -1858Marx, /1964Nussbaum, 1998) have prescribed a reduction in the incidence of objectification. The design and testing of intervention to reduce objectification are considered by many psychologists to be an important next step (e.g., Roberts & Waters, 2012). We, too, would like to ameliorate the negative outcomes of objectification.…”
Section: Should Psychologists Work To Reduce Objectification?mentioning
confidence: 99%